Agglomeration in Tourism Governance and Community Based Tourism in Nepal: An Ethnographic Reflection from Panauti Historical Area - Gautam, Sahadev (Nepalese Journal of Public Affairs, 2023)
Etymologically, tourism is an industry and part of recreation and the way for sustainable resource management at the local level through community participation. Community-based tourism in Nepal is famously known as homestay tourism. It is an agglomeration of much authentic cultural and ecological richness within diversity to the tourist’s experience at the exact moment to the local’s participation and empowerment. Homestay is a very potential rural and historical site-based tourism enterprise. Tourism governance is not isolated discourse; it has many tangible and intangible transactions. It has been a positive backbone for the growth of environmental tourism around the globe by utilizing and empowering the local community. The primary data was collected for my research work for my MPhil thesis. The article aims to assess the socioeconomic, cultural, and participation contribution of community-based tourism in Nepal, based on the ethnographic narration analysis design. Moreover, community-based tourism is not an isolated subject so tourism is highly accountable to income elasticity and local empowerment with local resource marketing and distribution. Findings show that homestays should have an eco-friendly infrastructure for sustainable resource mobilization and homestay as community-based tourism is community lead activities for the sake of empowerment of the local, especially women.